Kontribusi Hayat School dalam pengembangan kurikulum pendidikan Islam Era 4.0 - Ebi Nabilah; Hasan Basri (Ta'dibuna, 2021)
The purpose of this study was to find out the contribution of the nature school in the development of the Islamic education curriculum in the 4.0 era. This development was carried out in response to the challenges and effects of the 4.0 industrial revolution. The research was at the Hayat School of Nature. The curriculum used was is the 4V curriculum (Variety of activities, Variety of interactions, Variety of experiences, Variety of conflicts). The method used in this research is descriptive-analytical. The author collected various data from determined sources, then the data were processed to be something informative and as a final method, the data were analyzed to extract information and make decisions based on the data that had been analyzed. Data were collected through interviews, observation, and documentation studies. From the results of the study, it was found that the 4R curriculum is a manifestation of the development of the Islamic education curriculum at the Hayat School. All components of the 4R curriculum are following the transformation of Islamic education by remaining under the concept of a nature school. The 4R curriculum can also respond to the challenges and effects of the 4.0 industrial revolution, by looking at the core values at every level.   Abstrak Tujuan dari penelitian ini adalah untuk mengetahui kontribusi sekolah alam dalam pengembangan kurikulum pendidikan Islam di era 4.0. Pengembangan ini dilakukan guna merespons tantangan dan efek dari revolusi industri 4.0. Lokasi penelitian dilakukan di sekolah alam Hayat School. Kurikulum yang digunakannya yaitu kurikulum 4R (Ragam aktivitas, Ragam interaksi, Ragam pengalaman, Ragam konflik). Metode yang digunakan dalam penelitian ini adalah deskriptif analitis. Penulis mengumpulkan berbagai data dari sumber yang telah ditetapkan, kemudian data diolah sehingga menjadi sesuatu yang bersifat informatif dan terakhir data dianalisis untuk mengekstrak informasi dan mengambil keputusan berdasarkan data yang telah dianalisis. Pengumpulan data dilakukan melalui wawancara, observasi dan studi dokumentasi. Dari hasil penelitian, didapatkan bahwa kurikulum 4R merupakan wujud dari pengembangan kurikulum pendidikan Islam di sekolah alam Hayat School. Seluruh komponen kurikulum 4R sesuai dengan transformasi pendidikan Islam dengan tetap berada di bawah konsep sekolah alam. Kurikulum 4R juga dapat merespons tantangan dan efek dari revolusi industri 4.0, dengan melihat core value pada setiap jenjangnya.